North Korea's nuclear decisions and strategies : sovereignty, legitimacy, and the bomb - Hutchinson, George, 1963- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book provides a comprehensive analysis of North Korea's nuclear strategies and of the decisions which explain its strategic motivations. This book will be of interest to students in the fields of foreign policy, defense policy, nuclear proliferation, Korean Studies and International Relations"--
From Tributary to Colony to Divided State : Korean Sovereignty in a Changing World -- Liberated Korea in a Bipolar Atomic Order -- From Armistice to Atomic Ambitions : Planting the Seeds of Nuclear Latency -- Roots of Nuclear Resolve : Kim Il Sung's Proliferation Decision -- Seoul's Cold War Triumph and Pyongyang's Nuclear Subterfuge -- North Korea's Nuclear Path to Legitimacy -- Brinkmanship and Diplomacy : Negotiating with North Korea -- Kim Jong Il's Nuclear Acquisition Decision -- Kim Jong Un's Race Against Sanctions and the Ripening of North Korea's Nuclear Doctrine.
Keywords: Nuclear warfare -- Korea (North); National security -- Korea (North); Nuclear weapons -- Government policy -- Korea (North); Nuclear nonproliferation -- Korea (North); Korea (North) -- Defenses; Korea (North) -- Foreign relations -- 20th century; Korea (North) -- Foreign relations -- 21st century; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / International Relations / Arms Control; HISTORY / Asia / Korea